Design and development of high pressure natural gas injector model for single cylinder four stroke engine using matlab simulink - Mohd Nor Afiq, Nor Hashim (2012)
The aim of this project is to design and develop the hydraulic model for control oriented injector model for single cylinder four-stroke engine using Matlab Simulink. Injector plays significant role in determining engine performance by controlling the fuel supplied consequently the air to fuel ratio. In order to achieve acceptable accuracy for abroad range of engine speed the control of injection process must be carefully studied. The model consist of hydraulic, electromagnetic and mechanical model. This thesis is carried out with purpose to produces a reliable hydraulic model that can be used to study the control process. Reasonable mass flow rate data need to be determine by the model based on predetermined boundary condition. The fuel injector based on HDEV 5 were design using Matlab Simulink. The are two different Matlab Simulink design the fuel flow rate coresponding to the radius/diameter ratio and the fuel flow rate corresponding to the needle-seat relative displacement. Based on the graph and explanation, comparison between fuel flow rate and r/d ratio and fuel flow rate and needle-seat relative displacement are made. The result show that there is cavitation occur at r/d = 0.02 and effect the flow rate of the fuel injected. While in the injector opening phase, the fuel flow rate is slightly increase before the injector reached the transition value. The model of flow through the control volume feeding and discharge holes was further detailed as it was shown to play an important role in determining the flow regime in the orifice.